SOSIALISASI PENCEGAHAN DAN TERAPI PENYAKIT OSTEOARTHRITIS DI MASYARAKAT DUKUH MENANGGAL SURABAYA - Asri Wido Mukti; Prisma Trida Hardani; Asti Rahayu; Kharisma Auliya; Rahmaniyyah Wulandari Sambada (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
Osteoarthritis (OA) is the most common joint disorder and usually affects the hips, knees, hands and feet. In Indonesia, the prevalence of osteoarthritis reaches 5% at the age of 61 years. For knee osteoarthritis, the prevalence is quite high, namely 15.5% in men and 12.7% in women. Pain is usually the main symptom of Osteoarthritis. Based on the cause is divided into 2, namely primary and secondary osteoarthritis. Based on the location of the joints affected, namely: hands, knees, hips, vertebrae, feet and ankles, shoulders, elbows, temporomandibular. Clinical symptoms in Osteoarthritis that usually appear according to the 2014 IRA Recommendations are: OA pain caused by 3 major causes, morning stiffness, joint motion barriers, joint swelling, disturbances in daily activities. Prevention of osteoarthritis includes maintaining weight, in the elderly using a cane as a tool, protecting joints from injury, exercising regularly. The purpose of this community service is to provide insight to the community regarding the prevention and therapy of this Osteoarthritis disease. Increased public knowledge before and after the activity increased by 45%, public knowledge is also increasing in terms of using drugs to reduce pain from just letting the pain go away, then knowing about drugs that can be used to relieve pain experienced as well as treatments that can be used. This is done to nourish the bones so they don’t experience pain.